Childhood sexual abuse and bulimic behavior in a nationally representative sample. - Wonderlich, S A (1996)
OBJECTIVES. This study examines whether childhood sexual abuse is a significant risk factor for the development of bulimic behavior in women. METHODS. Interviews were conducted among a representative national sample of 1099 US women regarding their sexual experiences during childhood as well as their lifetime prevalence of bulimic behavior. Logistic regression was used to calculate adjusted odds ratios to measure the contribution of childhood sexual abuse to the odds of several measures of bulimic behavior in the population, controlling for the respondent's age, ethnic group, and parents' educational level. Attributable risk analyses were conducted to estimate how much risk for bulimic behavior was due to childhood sexual abuse. RESULTS. Victims of childhood sexual abuse were significantly more likely to display bulimic behavior, and a substantial fraction of cases of bulimic behavior could be attributed to such abuse. CONCLUSIONS. Childhood sexual abuse is a risk factor for bulimic behavior. Between one sixth and one third of the cases of significant bulimic disturbance could be attributed to childhood sexual abuse.